Incorporation of Heliospheric Imagery Into the CME Analysis Tool for Improvement of CME Forecasting. Issue 8 (24th August 2019) - Wharton, S. J.; Millward, G. H.; Bingham, S.; Henley, E. M.; Gonzi, S.; Jackson, D. R.
Abstract: Coronal mass ejections (CMEs) cause the largest geomagnetic disturbances at Earth, which impact satellites, wired communication systems, and power grids. The CME Analysis Tool (CAT) is used to determine a CME's initial longitude, latitude, angular width, and radial speed from coronagraph images. These are the initial conditions for the Wang‐Sheeley‐Arge Enlil solar wind model, along with the ambient solar wind properties derived from magnetograms. However, the coronagraph imagery is limited by field of view. We have incorporated heliospheric imagery (HI) from the Solar Terrestrial Relations Observatory into CAT to create the CME Analysis Tool with Heliospheric Imagery (CAT‐HI). These HI images have a larger field of view, allowing tracking of CMEs to greater distances from the Sun. We have compared the performances of CAT and CAT‐HI by examining the expected arrival times of CMEs at the L1 Lagrange point and found them to be consistent. However, CAT‐HI is advantageous because it could be used to prune ensemble forecasts and issue routine updates for CME arrival time forecasts. Finally, we discuss CAT‐HI in the context of an operational mission at the L4 or L5 Lagrange points. Plain Language Summary: Our Sun often releases large explosions of hot charged particles. These eruptions can travel through space all the way to the Earth. Here, they can damage satellites and disrupt communication systems and power grids. Therefore, we would like to predict their arrival  time accurately, but currently, this is difficult. At the moment, operators use a tool based on coronagraph images, which look at the atmosphere of the Sun. This allows them to see the eruptions leaving the Sun. However, coronagraphs have a limited field of view, so the operators quickly lose sight of the eruptions. In this work, we have added a new kind of imagery that directly images the eruptions in the space between the Sun and the Earth. This new tool will allow the operators to track the eruptions for longer and to update their predictions of when they will arrive at Earth. The new tool could also be used in conjunction with a dedicated operational mission to monitor these eruptions. In summary, we think that the new tool presented in this paper could be a major advance in our ability to forecast these violent ejections. Key Points: We developed a new CME analysis tool called CAT‐HI that incorporates Heliospheric Imagery from the STEREO spacecraft CAT‐HI could enable ensemble pruning when running ensemble forecasts for CMEs and trajectory corrections CAT‐HI could also be used in conjunction with a dedicated mission to L4 or L5